Physical Activity and Psychological Well-Being in Older University Office Workers: Survey Findings. (March 2019) - Qi, Meiling; Moyle, Wendy; Jones, Cindy; Weeks, Benjamin
Prolonged sitting time has been reported among university workers which can have adverse health effects. The aim of this study was to examine the sitting time, physical activity, and psychological well-being reported by older university office workers. An online self-reported survey was distributed to all office workers 55 years and older at one university in Australia. Sixty-six office workers were recruited. They reported an average sitting time of 7.5 hours per day on weekdays. In all, 72.7% of the sample reported both moderate and high physical activity levels. A high percentage of the office workers reported depression (25.8%) and anxiety (12.1%). Lower education levels were significantly related to higher perceived stress and more depressive symptomatology ( p = .03 and .02, respectively). Significant associations were found between stress, depression, and anxiety ( p < .001) among this group of workers.